MODES OF CORPOREALITY AND SPIRIT IN THE VIRTUAL SPACE OF JANUSZ LEON WIŚNIEWSKI’S ’S TALE «IN SEARCH OF THE MOST IMPORTANT» - Derkachova, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The purpose. The article deals with the features of corporeality and spiritual modes in Janusz Leon Wiśniewski’s fairy tale «In search of the most important», which is a synthesis of scientific, philosophical and religious principles. Attention is focused on understanding the concepts of virtual corporeality and virtual space in fiction, parallels between the simulation of the world of the Polish author’s fairy tale and the world of the computer game-quest are drawn. The structural features of the fairy tale and the means of characterization of the main characters are determined. Research methods. The research used a system of historical, hermeneutic and structural methods. The author relies on the theoretical-empirical scientific method, uses the methodology of literary cognitivism, which is determined by the specifics of literary research. Research results. The research makes it possible to reveal the features of corporeality in the virtual space, which can be defined as a simulacrum, an artificial construct with an avatar soul. The virtual space itself is imagined as a model of the universe with its special inhabitants. The design of the book, made in the style of net art, complements the visually artistic virtual space and creates the illusion of the reality of virtual bodies. The main character is looking for the meaning of life, the most important thing for her, not in basic reality, but in virtual space, but she understands that the identity she needs is in the real world, where she turns from the thought of a girl into a real girl. Originality of the study consists in an attempt to consider the secondary virtual reality created by the writer in the artistic world, not in the digital one, to trace the peculiarities of its modeling, to investigate the problem of the expressive and pictorial possibilities of the artistic word in combination with the corresponding illustrative material. The practical significance of the article lies in the possibility of using the research results in scientific researches and courses related to the study of Polish literature, the virtualization of space in fiction, the study of modes of physicality in real and virtual spaces.